2016
DOI: 10.1242/jeb.134437
|View full text |Cite
|
Sign up to set email alerts
|

Limits to sustained energy intake. XXIII. Does heat dissipation capacity limit the energy budget of lactating bank voles?

Abstract: Understanding factors limiting sustained metabolic rate (SusMR) is a central issue in ecological physiology. According to the heat dissipation limit (HDL) theory, the SusMR at peak lactation is constrained by the maternal capacity to dissipate body heat. To test that theory, we shaved lactating bank voles (Myodes glareolus) to experimentally elevate their capacity for heat dissipation. The voles were sampled from lines selected for high aerobic exercise metabolism (A; characterized also by increased basal meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 58 publications
1
25
0
Order By: Relevance
“…Our study showed that parous females revealed more profound differences in pubic size from males than nulliparous females. The difference is presumably primarily due to birth (Schilling 2005) and energy requirement of reproducing females (Kaczmarski 1966;Sadowska et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that parous females revealed more profound differences in pubic size from males than nulliparous females. The difference is presumably primarily due to birth (Schilling 2005) and energy requirement of reproducing females (Kaczmarski 1966;Sadowska et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, such studies have generated inconsistent results. In MF1 mice20 and bank voles21 shaving elevated milk production and pup growth. In short-tailed field voles shaving elevated pup growth but a small impact on milk production did not reach significance19.…”
mentioning
confidence: 92%
“…A different peripheral constraint restricting reproductive performance, maternal hyperthermia during lactation, was studied in the early 1980s (Leon et al, , 1985(Leon et al, , 1990Croskerry et al, 1978;Woodside et al, 1980;Jans and Leon, 1983a,b; and has gained attention more recently as the 'heat dissipation limit' (HDL) hypothesis (Hammond et al, 1996;Król and Speakman, 2003a,b;Król et al, 2007;Król, 2010, 2011;Ohrnberger et al, 2016;Sadowska et al, 2016). It promotes the idea that a lactating mother's performance is bound by her ability to dissipate excessive amounts of heat generated during milk synthesis and energy turnover Król, 2010, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results thus far have been equivocal. A number of studies reported elevated milk production and heavier litters in mothers placed in colder environments Król and Speakman, 2003b;Valencak et al, 2010;Valencak et al, 2013) as well as in mothers with thermal conductance enhanced by shaving (Król et al, 2007;Sadowska et al, 2016). Other papers, however, failed to demonstrate any effects of shaving or placing the lactating mother at lower ambient temperature on her parental effort (Zhao and Cao, 2009;Zhao, 2011Zhao, , 2012.…”
Section: Introductionmentioning
confidence: 99%